microRNAs: key triggers of neuronal cell fate - Meza-Sosa, Karla F.; Pedraza-Alva, Gustavo; Pérez-Martínez, Leonor (Frontiers in Cellular Neuroscience, 2014)
Development of the central nervous system requires a precisely coordinated series of events. During embryonic development, different intra- and extracellular signals stimulate neural stem cells to become neural progenitors, which eventually irreversibly exit from the cell cycle to begin the first stage of neurogenesis. However, before this event occurs, the self-renewal and proliferative capacities of neural stem cells and neural progenitors must be tightly regulated. Accordingly, the participation of various evolutionary conserved microRNAs is key in distinct CNS developmental processes of many organisms including human, mouse, chicken, frog and zebrafish. microRNAs specifically recognize and regulate the expression of target mRNAs by sequence complementarity within the mRNAs 3’ untranslated region and importantly, a single microRNA can have several target mRNAs to regulate a process; likewise, a unique mRNA can be targeted by more than one microRNA. Thus, by regulating different target genes, microRNAs let-7, microRNA-124 and microRNA-9 have been shown to promote the differentiation of neural stem cells and neural progenitors into specific neural cell types while microRNA-134, microRNA-25 and microRNA-137 have been characterized as microRNAs that induce the proliferation of neural stem cells and neural progenitors. Here we review the mechanisms of action of these two sets of microRNAs and their functional implications during the transition from neural stem cells and neural progenitors to fully differentiated neurons. The genetic and epigenetic mechanisms that regulate the expression of these microRNAs as well as the role of the recently described natural RNA circles which act as natural microRNA sponges regulating post-transcriptional microRNA expression and function during the early stages of neurogenesis is also discussed.